The Role of the External Auditor’s Report in Supply Chain Management - Muayad abdulameer habeeb, Ihsan abdulhamza khamees, Reah chafat Abdullah, (Opción, 2019)
The subject of the research is to evaluate the effect of the external auditor’s report as the main supply chain management on the performance of organizations via comparative qualitative research methods. The results indicate that the external auditor’s report has a direct and positive effect on the performance of the organization if it is considered reliable by the users of accounting information. In conclusion, investing only on information technology is not enough, but fundamental changes in the physical aspects of the supply chain may be necessary